THE SACRED NAME ON THE BOTTLE: Perspektif Semiologi Saussurean dalam Kampanye Marketing Holywings Indonesia - Audita Ressa Affanda; Moh. Atikurrahman (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
This research focuses on Instagram uploads from Holywings Indonesia which juxtapose two sacred names (Muhammad and Maria) with bottles of liquor (Gordon's Gin). The promotional upload then went viral until Holywings Indonesia was deemed to have blasphemed religion. This paper places the Holywings Indonesia promotional upload as a material object of semiotic studies. In the researcher's opinion, these uploads represent sign phenomena and tagging systems. Every language expression, image, color, and so on has a basis of meaning implied behind the sign. For research purposes, Saussure's scheme of signs (semiology) is used as a methodological tool in understanding the meaning of signs (markers and signifieds) uploaded by the Holywings Marketing Campaign.